2020
DOI: 10.1681/asn.2019050523
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endothelial PHD2 Suppresses Post-Ischemic Kidney Inflammation through Hypoxia-Inducible Factor-1

Abstract: BackgroundProlyl-4-hydroxylase domain-containing proteins 1–3 (PHD1 to PHD3) regulate the activity of the hypoxia-inducible factors (HIFs) HIF-1 and HIF-2, transcription factors that are key regulators of hypoxic vascular responses. We previously reported that deficiency of endothelial HIF-2 exacerbated renal ischemia-reperfusion injury, whereas inactivation of endothelial PHD2, the main oxygen sensor, provided renoprotection. Nevertheless, the molecular mechanisms by which endothelial PHD2 dictates AKI outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…During this process they undergo activation with increased expression of adhesion molecules, causing the recruitment and activation of inflammatory cells. Recently, Rajendran et al [ 43 ] investigated the effects of endothelial-specific ablation of PHD2 in a mouse model of renal ischaemia–reperfusion injury. This was found to improve early and late damages occurring during AKI, thanks to the suppression of the expression of proinflammatory genes and recruitment of inflammatory cells in a HIF-1α-dependent manner.…”
Section: The Hif System and Akimentioning
confidence: 99%
“…During this process they undergo activation with increased expression of adhesion molecules, causing the recruitment and activation of inflammatory cells. Recently, Rajendran et al [ 43 ] investigated the effects of endothelial-specific ablation of PHD2 in a mouse model of renal ischaemia–reperfusion injury. This was found to improve early and late damages occurring during AKI, thanks to the suppression of the expression of proinflammatory genes and recruitment of inflammatory cells in a HIF-1α-dependent manner.…”
Section: The Hif System and Akimentioning
confidence: 99%
“…Hypoxia contributes to VC by inducing osteochondrogenic differentiation of VSMC in a HIF-1a–dependent and mitochondria-derived reactive oxygen species–dependent manner [ 21 ]. Of the three PHD isoforms, PHD2 appears to be the primary HIF-1a hydroxylase based on genetically engineered mice and cell culture studies [ 46 ]. In the present study, we have shown that the PHD2 regulated PFKFB3 expression in VSMCs during calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the role of HIF in cisplatin-induced nephrotoxicity, targeting or activating HIF and its related pathways may be a therapeutic strategy. PHD-pVHL pathway plays a vital role in HIF regulation, and pharmacological or genetic inhibition of PHD activity is under intensive research in kidney diseases [ 18 , 45 , 167 , 168 , 181 , 182 , 183 , 184 , 185 ]. The role of regulating HIF in cisplatin-induced nephrotoxicity is summarized in Table 1 ; besides the evidence that HIF accumulation by PHD inhibitors treatment protects against cisplatin-induced nephrotoxicity [ 18 ], studies have reported beneficial effects of PHD inhibitors in other kidney diseases including ischemic AKI [ 167 , 168 ], diabetic nephropathy [ 182 , 183 ], obesity related kidney disease [ 181 ], chronic tubulointerstitial nephritis [ 184 ], and remnant kidneys models of CKD [ 186 ].…”
Section: Therapeutic Potential Of Hif In Cisplatin Chemotherapymentioning
confidence: 99%